Understanding conflicting outcomes in common property based natural resources management in South Africa : comparative analysis of Bela-Bela and Bjatladi Communal Property Associations - Mungatana, Eric D. (University of Pretoria, 2016)
Dissertation (MSc Agric)--University of Pretoria, 2016.